ANALYSIS REGARDING THE EVOLUTION OF THE CEREAL SECTOR IN THE NORTH-EAST REGION OF ROMANIA - Irina-Adriana CHIURCIU; Elena SOARE; Dana Maria (Oprea) CONSTANTIN; Elena GRIGORE; Elena BOGAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper analyzed the evolution of the cereal sector in the North-East Region of Romania, in the period 2015-2019. In order to carry out a more realistic study, a series of quantitative indicators specific to the cereal sector were analyzed. Also, the factors that directly influenced the results obtained in this sector were highlighted. In the North-East Region, the corn crop is on the first place in the ranking of cereal crops. This culture also holds a significant place at the macro-regional level. In 2019, in the North-East Region, 464,008 ha were cultivated with corn out of a total of 966,729 ha, cultivated in Macroregion Two, which represents 48%. A significant role in the economy of the cereal sector in the North-East region is played by the wheat culture. In this region, in 2019, 25.78% of the areas related to this cereal crop registered at the level of the Macroregion Two were cultivated. The largest productions were made at the corn crop. The productions made for this crop in 2019 were differentiated at the level of the counties in this region. The increase of the productivity of all medium and long-term cereal crops will be possible if farmers adopt an agriculture, in which new technologies will occupy a central place. The data used in the paper were collected from the National Institute of Statistics.